Desensitization of skate photoreceptors by bleaching and background light (The Rockefeller University Press, 1982)
Through extracellular measurements of photoreceptor responses to flashed stimuli, we examined how the bleaching of rhodopsin affects increment receptor threshold in the isolated retina of the skate (Raja oscellata and R. erinacea). Both initially unbleached and previously bleached photoreceptors, when exposed to full-field luminous backgrounds of fixed intensity, attain approximately stable levels of increment threshold that vary with the intensity of the background light. Values of stabilized increment thresholds measured after various extents of bleaching (less than approximately 50%), when plotted against background intensity in log-log coordinates, tend to converge with increasing intensity of the background; this relationship of the increment threshold functions resembles that which Blakemore and Rushton (1965b) found to describe the transient effect of bleaching on psychophysical increment threshold for the human rod mechanism. Our data are consistent with the possibility that related photochemical processes govern the stabilized levels of receptor sensitivity exhibited by the isolated retina (a) during steady illumination and (b) long after substantial bleaching.